Serum Vascular Endothelial Growth Factor (Vegf) Levels and Alberta Stroke Program Early CT Score (Aspects) in Ischemic Stroke Patients - Fakhri M, Faisal; Bahar, Ashari; Bintang, Andi Kurnia; Walenna, Nirwana Fitriani; Tammasse, Jumraini; Muis, Abdul (Sarana Ilmu Indonesia (salnesia), 2024)
Stroke is the second leading cause of death and disability worldwide. Where the most common occurrence of ischemic stroke is 85% of all stroke cases. Vascular Endothelial Growth Factor (VEGF) is a dimeric glycoprotein with angiogenic and neuroprotective effects. Alberta Stroke Program Early CT Score (ASPECTS) can be used to assess the extent of acute ischemic stroke in the middle cerebral artery territory as a simple semiquantitative instrument. Method a cross-sectional study in acute ischemic stroke patients with an onset of 3-14 days. The VEGF assessed was serum VEGF and ASPECTS assessment to determine the extent of the lesion. Total ASPECT score is 10 points (normal), score > 7 (lesion area < 1/3 MCA), score < 7 (lesion area > 1/3 MCA). Of the 37 patients, the majority of patients were women (62,2%) with hypertension being the most common comorbid. All risk factors had no significant relationship to VEGF levels (p-value>0,005). There was a significant difference between the two ASPECTS categories on serum VEGF levels (p-value=0,001), A significant correlation occurred in serum VEGF levels with ASPECTS (p-value=0,000; r-0,600). Conclusion higher VEGF levels increase cerebral infarction.